Targeting Phosphodiesterase 4 in Gastrointestinal and Liver Diseases: From Isoform-Specific Mechanisms to Precision Therapeutics - Can Chen; Mei Liu; Xiang Tao (Biomedicines, 2025)
Phosphodiesterase 4 (PDE4) serves as a crucial regulator of cyclic adenosine monophosphate (cAMP) signaling and has been identified as a significant therapeutic target for inflammatory and metabolic disorders impacting the gastrointestinal (GI) tract and liver. Although pan-PDE4 inhibitors hold therapeutic promise, their clinical use has been constrained by dose-dependent adverse effects. Recent progress in the development of isoform-specific PDE4 inhibitors, such as those selective for PDE4B/D, alongside targeted delivery systems like liver-targeting nanoparticles and probiotic-derived vesicles, is reshaping the therapeutic landscape. This review consolidates the latest insights into PDE4 biology, highlighting how the structural characterization of isoforms informs drug design. We conduct a critical evaluation of preclinical and clinical data across various diseases, including inflammatory bowel diseases (IBDs), alcoholic liver disease, nonalcoholic fatty liver disease (NAFLD), liver fibrosis, and digestive tract tumors, with an emphasis on mechanisms extending beyond cAMP modulation, such as microbiota remodeling and immune reprogramming. Additionally, we address challenges in clinical translation, including biomarker discovery and the heterogeneity of trial outcomes, and propose a roadmap for future research directions.